The role of autonomic nervous system in susceptibility and resilience to stress. (April 2017) - Pereira, Vitor H; Campos, Isabel; Sousa, Nuno
Highlights: Chronic stress increases the risk of neuropsychiatric, cardiovascular and endocrine disorders. The susceptibility to chronic stress varies among individuals and changes across lifespan. Stress resilience can be modulated through distinct molecular mechanisms. The autonomic nervous system is a target and a determinant of stress resilience and its manipulation using biofeedback is useful to promote resilience. Abstract : Chronic stress increases the risk of neuropsychiatric, cardiovascular and endocrine diseases. Interestingly, the susceptibility to stress among individuals is variable and only some experience stress-related diseases. The determinants of resilience (the concept of resistance to chronic stress) are still not well understood. Their knowledge may contribute to the development of strategies to tackle stress-related disorders from a preventive perspective. Recent evidences show that the autonomic nervous system may play a role in the susceptibility to stress and may be used as a marker of resilience. Departing from that point, this short review will provide a perspective of the role of the autonomic nervous system in the susceptibility to the stress response.